7 DOACs: a new skyline in cancer-associated thrombosis resistant to heparin. A clinical case of seminoma in BEP chemotherapy protocol solved with edoxaban. (8th December 2021) - Fioretti, Agnese Maria; Leopizzi, Tiziana; Sarcinella, Gianvito; Giotta, Francesco; Lorusso, Vito; Oliva, Stefano
Abstract: Aims: TEV is a common cancer complication with 20% incidence. LMWH is the standard therapy for efficacy, safety and ease of use. However, some scenarios are deeply challenging for intercurrent prothrombotic anticancer drugs. Methods: A 35-year-old man reported dysphagia, EGDS: oesophagus ulcers, thyroid echography: thoracic mass compressing proximal borders. Vascular ultrasound: thrombosis of left internal giugular, subclavian, axillary and brachial veins; he began enoxaparin 6000 IU ×2/die (65 kg). CT-scan: solid anterior–superior mediastinum vascularized mass (16 × 13 cm) incorporating great thoracic vessels with 20 cm cranio-caudal longitudinal extension with trachea dislocation. PET-CT: massive superior-anterior mediastinum pathological 18 F-FDG accumulation suggestive for malignancy. Lung perfusion scan: absence of left lung perfusion. Angio-CT: showed compression of pulmonary artery trunk and of branches. He presented marked asthenia, sweating and presyncope. D-dimer: 6026 µg/L, NT-proBNP: 1417 pg/mL. Mediastinum biopsy exhibited seminoma (ki67+: 65%), he started BEP Protocol (etoposide, cisplatin, bleomycin). TTE: periaortic cuff from mediastinum mass which ab extrinseco compressed pulmonary artery trunk and branches with occlusion of left one, right chambers dilatation, sovra-epatic veins and inferior vena cava (21 mm) ectasia, decreased inspiratory collapse, pulmonary hypertension (SPAP: 52 mmHg), EF: 55%. After 2 months of enoxaparin, vein ultrasound: persistent DVT and positive CUS. So, we replaced enoxaparin with edoxaban 60 mg/die. After 2 months of edoxaban, overall regression of vein thrombosis with minimal residual thrombosis of left internal giugular vein; D-dimer: 1554 µg/L. Results: After 2 months of BEP Protocol, CT-scan: decrease mediastinum mass (6 × 12 cm) dimensions. Conclusions: Cancer associated thrombosis is a frequent complication, worsening mortality, morbidity and decision-making. Cancer stage and drugs favour development of severe thrombosis, not solvable with LMWH, the cornerstone of anticoagulant therapy in cancer-related thrombosis. DOACs appear as a new and successful therapeutical option, especially in the most challenging cases of highly thrombotic profile after 'heparin failure'.